Development of Digital LKPD with a Scientific Approach to Mushroom Materials for High School Students Class X - Arief Widiyantoro; Hani Irawati (Pusat Publikasi Nusantara, 2024)
This study aims to evaluate the quality of the digital student activity sheet (LKPD) focused on mushroom materials, as assessed by experts and teachers; to gather students' responses to the digital LKPD utilizing a scientific approach; and to assess the overall feasibility of this digital KTPD in enhancing the learning process related to mushroom materials. This research has been carried out in the form of a 4-D development model. The evaluation of material experts received a percentage of 88.02% with a very good category, so this teaching material is suitable for use as a class x teaching material for mushroom material. The average of the small group test and the large group test was declared very good. The feasibility aspect of the scientific approach received 95.00% with the category of very good and the aspect of ability received 85.00%. The long-term impact study could measure knowledge retention, engagement, and application of concepts over time. This study could explore the potential for cross-curricular connections, particularly with environmental science or technology, to enhance students' understanding of fungal materials and their applications.